2012
DOI: 10.1162/jocn_a_00269
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Functional Connectivity by Aging Is Associated with Cognitive Decline

Abstract: Aging is related to cognitive decline, and it has been reported that aging disrupts some resting state brain networks. However, most studies have focused on the default mode network and ignored other resting state networks. In this study, we measured resting state activity using fMRI and explored whether cognitive decline with aging is related to disrupted resting state networks. Independent component analysis was used to evaluate functional connectivity. Notably, the connectivity within the salience network t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
254
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(300 citation statements)
references
References 61 publications
39
254
3
4
Order By: Relevance
“…In contrast, during EM and SM trials, the aIFO seeds were functionally connected with premotor and temporal areas. It is not clear what type of mechanism this pattern reflects, but it may indicate that different search processes are engaged when participants struggle to retrieve a non-personal memory.We found no evidence for age differences in the strength of functional connectivity within the core SLN, either during the incorrect trials or in the estimate of intrinsic functional connectivity, although a number of studies have reported such age differences (Allen et al, 2011; Geerligs et al, in press;He et al, 2014;Meier et al, 2012;Onoda et al, 2012;Tomasi and Volkow, 2012). Although we did not find age differences in the primary pattern of connectivity within the SLN, we did see reductions in the strength of connectivity between the aIFO seeds and regions outside the SLN, as well as a lack of task-specificity in the pattern of connectivity across the three memory conditions in older adults.…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…In contrast, during EM and SM trials, the aIFO seeds were functionally connected with premotor and temporal areas. It is not clear what type of mechanism this pattern reflects, but it may indicate that different search processes are engaged when participants struggle to retrieve a non-personal memory.We found no evidence for age differences in the strength of functional connectivity within the core SLN, either during the incorrect trials or in the estimate of intrinsic functional connectivity, although a number of studies have reported such age differences (Allen et al, 2011; Geerligs et al, in press;He et al, 2014;Meier et al, 2012;Onoda et al, 2012;Tomasi and Volkow, 2012). Although we did not find age differences in the primary pattern of connectivity within the SLN, we did see reductions in the strength of connectivity between the aIFO seeds and regions outside the SLN, as well as a lack of task-specificity in the pattern of connectivity across the three memory conditions in older adults.…”
contrasting
confidence: 69%
“…Age differences in functional connectivity have been examined extensively for the default network (e.g., Andrews-Hanna et al, 2007;Damoiseaux et al, 2008;Grady et al, 2012), and to some extent for other brain networks (Allen et al, 2011;Campbell et al, 2012;Onoda et al, 2012;Rieckmann et al, 2011;Thomas et al, 2013;Tomasi and Volkow, 2012;Voss et al, 2010). Weaker functional connectivity has been reported specifically within the SLN or in SLN nodes in older adults (Allen et al, 2011;Geerligs et al, in press;He et al, 2014;Meier et al, 2012;Onoda et al, 2012;Tomasi and Volkow, 2012), leading us to predict age-related reductions in SLN functional connectivity in our results, although connectivity within the striatum, a node of the SLN, has been shown to increase with age (Allen et al, 2011;Tomasi and Volkow, 2012;Wang et al, 2012). However, most of these earlier studies examined resting-state functional connectivity, and it is unclear whether similar age reductions would be found during our tasks, on which there were no age differences in overall accuracy or response times (St-Laurent et al, 2011).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the energy probabilities of the visual network declined, while the energy probabilities of the default, frontoparietal, and limbic networks decreased further. This result may be consistent with the further enhanced heterogeneity of whole-brain functional subsystems [60][61][62][63][64][65]. The values of EP in the brain regions of the frontoparietal network increased slightly.…”
Section: The Orderness Variability Of Functional Subsystems With Agesupporting
confidence: 82%
“…These three neural networks are central to cognition, as they are engaged in a large number of functions, and their disruption has been associated with a variety of clinical syndromes, such as schizophrenia, traumatic brain injury, and Alzheimer's disease (Manoliu et al, 2014;Sharp et al, 2014;Zhou et al, 2010). In addition, evidence suggests that the disruption of the dynamic coordination of these large-scale networks constitutes one of the main causes of cognitive decline associated with ageing (Andrews-Hanna et al, 2007;Sambataro et al, 2010), as shown by reduced neural activity in the DMN and SN at rest (Allen et al, 2011;Onoda et al, 2012) and RESTING STATE NETWORKS IN THE AGEING BRAIN 4 increased activity in the FPN of older adults during visual tasks .…”
Section: Introductionmentioning
confidence: 99%